The Relationship of Mind Mapping Learning Methods During the Covid-19 Pandemic With Science Learning Outcomes of Class 5 Students in Elementary Schools: Hubungan Metode Pembelajaran Mind Mapping Pada Masa Pandemi Covid-19 Dengan Hasil Belajar IPA Siswa Kelas 5 di Sekolah Dasar - Sisfia Titis Zurachman; Fitria Wulandari (Academia Open, 2022)
This study aims to determine whether there is a relationship between the mind mapping learning method during the covid-19 pandemic with students' science learning outcomes, and how strong is the relationship between mind mapping learning methods during the covid-19 pandemic and students' science learning outcomes. The research method used in this research is non-experimental quantitative. Data collection techniques using questionnaires and learning outcomes tests. Data analysis using SPSS 25. The sample in this study amounted to 20 students. In this study, the research results obtained from the product moment correlation test results, namely r-count (0.567) > r-table (0.444) with a significant level of 5%. Based on the results of the research and the results of the product moment correlation test that has been carried out, it can be concluded that there is a fairly strong relationship between the mind mapping learning method during the COVID-19 pandemic and students' science learning outcomes.